2018
DOI: 10.1159/000489447
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-Gallate Regulates Anti-Inflammatory Action Through 67-kDa Laminin Receptor-Mediated Tollip Signaling Induction in Lipopolysaccharide-Stimulated Human Intestinal Epithelial Cells

Abstract: Background/Aims: Inflammatory bowel disease (IBD) is a condition that involves chronic inflammation in all or part of the digestive tract. Often painful and debilitating, IBD can lead to life-threatening complications and increase the risk for colon cancer. In this study, we investigated the epigallocatechin-3-gallate (EGCG) mediated anti-inflammation response in lipopolysaccharide (LPS)-stimulated human colorectal cells through the negative regulator of Toll-like receptor (TLR) signaling. Methods: human intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…67LR is a membrane receptor of EGCG 22 and EGCG was reported to trigger cell death via 67LR in multiple types of tumour cells 23,36 . Previous studies showed that EGCG could activate the 67LR signalling pathway to inhibit inflammation in endothelial cells 27 , adipocytes 26 and intestinal epithelial cells 37 . EGCG remarkably decreased oxidative stress and inflammation levels through 67LR in an acute lung injury mouse model 24 , and EGCG inhibited H 2 O 2 -induced apoptosis via 67LR in mouse vascular smooth muscle cells, indicating that the antioxidant effect of EGCG is associated with 67LR 25 .…”
Section: Discussionmentioning
confidence: 99%
“…67LR is a membrane receptor of EGCG 22 and EGCG was reported to trigger cell death via 67LR in multiple types of tumour cells 23,36 . Previous studies showed that EGCG could activate the 67LR signalling pathway to inhibit inflammation in endothelial cells 27 , adipocytes 26 and intestinal epithelial cells 37 . EGCG remarkably decreased oxidative stress and inflammation levels through 67LR in an acute lung injury mouse model 24 , and EGCG inhibited H 2 O 2 -induced apoptosis via 67LR in mouse vascular smooth muscle cells, indicating that the antioxidant effect of EGCG is associated with 67LR 25 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, dietary naringenin induces T regulatory (Treg) cells binding to intestinal AhR [75]. Furthermore, EGCG is able to bind to the 67 kDa laminin receptor, the zeta-chain-associated 70kDa protein (ZAP-70), and the retinoic acid-inducible gene (RIG)-I, respectively [75][76][77]. Neutrophils, monocytes/macrophages, mast cells, and T cells express ZAP-70 [78,79].…”
Section: Receptors For Polyphenolsmentioning
confidence: 99%
“…Epigallocatechin-3-gallate found in green tea can regulates anti-inflammatory action through laminin receptor-mediated tollip signaling induction in LPS-stimulated human intestinal epithelial cells [157]. Epigallocatechin-3-gallate (25-50 µM) can also suppress nicotine-induced migration and invasion by blocking angiogenesis and EMT of non-small cell lung carcinoma (NSCLC) cells [158].…”
Section: Reversal Of Emt By Anti-inflammatory Natural Compoundsmentioning
confidence: 99%